DNA methylation stability in fish spermatozoa upon external constraint: Impact of fish hormonal stimulation and sperm cryopreservation. Issue 1 (20th November 2019) - Depincé, Alexandra; Gabory, Anne; Dziewulska, Katarzyna; Le Bail, Pierre‐Yves; Jammes, Hélène; Labbé, Catherine
Abstract: Highly differentiated mature spermatozoa carry not only genetic but also epigenetic information that is to be transmitted to the embryo. DNA methylation is one epigenetic actor associated with sperm nucleus compaction, gene silencing, and prepatterning of embryonic gene expression. Therefore, the stability of this mark toward reproductive biotechnologies is a major issue in animal production. The present work explored the impact of hormonal induction of spermiation and sperm cryopreservation in two cyprinids, the goldfish ( Carassius auratus ) and the zebrafish ( Danio rerio ), using LUminometric Methylation Assay (LUMA). We showed that while goldfish hormonal treatment did increase sperm production, it did not alter global DNA methylation of spermatozoa. Different sperm samples repeatedly collected from the same males for 2 months also showed the same global DNA methylation level. Similarly, global DNA methylation was not affected after cryopreservation of goldfish spermatozoa with methanol, whereas less efficient cryoprotectants (dimethylsulfoxide and 1, 2‐propanediol) decreased DNA methylation. In contrast, cryopreservation of zebrafish spermatozoa with methanol induced a slight, but significant, increase in global DNA methylation. In the less compact nuclei, that is, goldfish fin somatic cells, cryopreservation did not change global DNA methylation regardless of the choice of cryoprotectant. To conclude, global DNA methylation is a robust parameter with respect to biotechnologies such as hormonal induction of spermiation and sperm cryopreservation, but it can be altered when the best sperm manipulation conditions are not met.